Optimisation of Graphene Nanofiller Addition on the Mechanical and Adsorption Properties of Woven Banana/Polyester Hybrid Nanocomposites by Grey-Taguchi Method - L. Natrayan; P. V. Arul Kumar; S. Kaliappan; S. Sekar; Pravin P. Patil; G. Velmurugan; Murtesa Dabesa Gurmesa (Adsorption Science & Technology)
Throughout history, techniques have shifted from mainstream metals and minerals to nanocomposites to generate smaller, more practical elements for particular purposes. Natural fibres have greater advantages than glass fibres, such as being cheaper, recyclable, and nonflammable. The main objective of the current experiment is to determine how the accumulation of graphene to hybrid polyester composites reinforced with woven banana fibre affects their mechanical properties. Composites were constructed utilising the hand lay-up process with the following limitations: (i) graphene filler weightiness, (ii) woven banana fibre thickness in gsm, and (iii) number of woven banana layers, all at three different levels. Using the L9 (33) orthogonal design, nine composite samples are generated and tested according to the ASTM standard. According to the grey research, hybrid composites having 5% graphene powder and 350 grammes per square metre of woven banana fibre in three layers have high mechanical strength. Adding fibre content to immaculate polyester increased its mechanical properties in general. As the fibre and filler concentrations grew, more energy was required to break the fibre bundles between the matrix and its resin. The confirmation test by the optimal process value utilising the grey relation analysis is considerably better than the actual test data. Tension strength has improved by 17.14%, bending strength has improved by 96.75%, and impact energy has increased by 16.17%.